Fruits and vegetables for sustainable healthy diets: WP3: Piloting and scaling of safe and sustainable vegetable production in the Philippines - University of the Philippines Los Baños; Department of Agriculture, Philippines (International Food Policy Research Institute, 2024)
Presentation given at World Vegetable Center in November 2024 for CGIAR FRESH Initiative.